إسلامية المعرفة في مؤسسات التعليم العالي باليمن : جامعة صنعاء نموذجا - مقبل، شيماء أحمد عبدالله (al-Ma'had al-'Alami lil-Fikr wa-al-Hadarat al-Islamiyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study aims to investigate the perceptions and opinions of the lecturers in the Faculties of Arts and Education at Sana'a University on the issue of the Islamization of knowledge and the methods in which they use to achieve this purpose, in addition, to test whether the departments that they are attached to effect their responses. The study has used the descriptive approach and the data was collected by conducting interviews with the lecturers. The total number of the lecturers that were interviewed in the current study was 22 lecturers, 9 lecturers were from the Faculty of Education and 22 lecturers were from the Faculty of Arts. The researcher has developed the questions of the interview; which they were categorized into three dimensions: necessity and need for the Islamization of knowledge, possibility of implementing the Islamization of knowledge, and strategies and approaches which use by the lecturers to implement the Islamization of knowledge. One of the most important findings of the study is that the majority of lecturers expressed their acceptance of the idea of the Islamization of knowledge and they believe in the need for it, despite the differences in their perceptions and opinions towards the Islamization of knowledge. In addition, they feel that the implementation of the Islamization of knowledge requires a lot of effort and special training. Furthermore, the study found that the lecturers are aware of the importance of the Islamization of knowledge as they believe that it should be included in the educational system as it will help Muslim students to redirect the Western knowledge in accordance with the Islamic principles. Moreover, the study found that the lecturers are implementing the Islamization of knowledge based on their personal efforts within the context of the courses they are teaching, in addition, there are no programs or scientific committees in the Faculties of Arts and Education to implement the project of Islamization of knowledge. The study recommended that the university should coordinate with the other centers of Islamization of knowledge to design a module on the issues of Islamization of knowledge which should be taught to students in the relevant departments such as Islamic studies, social science, and human science. In addition, the study also recommended establishing centers for the Islamization of knowledge by the university and preparing specialized studies, research and seminars in the field of Islamization of knowledge. Furthermore, it recommended to held courses and conferences which should be attended by lecturers and students to find methods to implement the Islamization of knowledge. Finally, it recommended encouraging the authorship and publication in universities on the issues related to the Islamization of knowledge.